The Status of the Abyssinian Caliphate in the Fourth and Tenth Centuries (Massachusetts) - ر, كەیوان ئازاد ئەنوه; ئەحمەد, هیوا مەحموود (Sulaimani Journal for Humanities, 2020)
In order to shed light on the most important factors behindthe development of Islamic thought and civilization in the 4th century AH/ 10th century AD, we have extracted this chapter entitled “The circumstances of the Abbasid Caliphate during the 4th century AH/ 10th century AD” from the MA thesis of the student (Hiwa Mahmmud Ahmed), supervised by (Ass. Prof. Dr. Kaiwan Azad Anwer). The current research has been re-formulated into three new divisions,; sheds light on the (political, economic, social, religious, and intellectual perspectives) during Abbasid caliphate. In addition to writing introduction, view most important resuits and refernces used in purly in research.